The Budyko shape parameter as a descriptive index for streamflow loss - Tran, Hoang; Yang, Chen; Condon, Laura E.; Maxwell, Reed M. (Frontiers in Water, 2023)
Increases in evapotranspiration (ET) from global warming are decreasing streamflow in headwater basins worldwide. However, these streamflow losses do not occur uniformly due to complex topography. To better understand the heterogeneity of streamflow loss, we use the Budyko shape parameter (ꞷ) as a diagnostic tool. We fit ꞷ to 37-year of hydrologic simulation output in the Upper Colorado River Basin (UCRB), an important headwater basin in the US. We split the UCRB into two categories: peak watersheds with high elevation and steep slopes, and valley watersheds with lower elevation and gradual slopes. Our results demonstrate a relationship between streamflow loss and ꞷ. The valley watersheds with greater streamflow loss have ꞷ higher than 3.1, while the peak watersheds with less streamflow loss have an average ꞷ of 1.3. This work highlights the use of ꞷ as an indicator of streamflow loss and could be generalized to other headwater basin systems.